2011
DOI: 10.1089/apc.2010.0333
|View full text |Cite
|
Sign up to set email alerts
|

Factors That Influence Risky Sexual Behaviors Among Men Who Have Sex with Men in Liaoning Province, China: A Structural Equation Model

Abstract: HIV prevalence among men who have sex with men (MSM) has increased rapidly in China. Behavioral and biologic interventions are the key to control the spreading of HIV in the MSM population and the primary strategy for reducing the spread of AIDS in China. The objective of this study is to explore the relationship among HIV-related knowledge, the basic information of respondents, service utilization and risky sexual behavior. Respondent-driven sampling was used to recruit 225 MSM in Fushun and Huludao in China.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 37 publications
2
6
0
Order By: Relevance
“…A study conducted in Liaoning province indicates that risky sexual behaviors might be indirectly reduced by improving HIV/AIDS-related knowledge [33]. In the present study, we also found that lower levels of HIV/AIDS-related knowledge are important risk factors for HIV infection.…”
Section: Discussionsupporting
confidence: 78%
“…A study conducted in Liaoning province indicates that risky sexual behaviors might be indirectly reduced by improving HIV/AIDS-related knowledge [33]. In the present study, we also found that lower levels of HIV/AIDS-related knowledge are important risk factors for HIV infection.…”
Section: Discussionsupporting
confidence: 78%
“…33,34 Interventions of this type might utilize peer based health education and counseling. 47,48 In addition, our finding also showed that persons buying condoms in the past 12 months had a lower HIV prevalence compare to those who never bought condoms. Our study and the previous studies among Chinese MSM showed high proportion of unprotected sex with male and female.…”
Section: Discussionsupporting
confidence: 63%
“…As we rarely know the accurate characteristics and the size of the MSM population, we could hardly verify whether the sample included all MSM networks [47]. Moreover, both univariable and multivariable analyses in this study were conducted by applying RDSAT-generated weights to dependent variables only (e.g., HIV infection) as much of the comparable literature has done [48], [49], [50]. However, such application is still under development and requires further validation.…”
Section: Discussionmentioning
confidence: 99%